Wear and corrosion behaviour of Ti-based coating on biomedical implants. (2nd January 2021) - Godwin, G.; Jaisingh, S. Julyes; Priyan, M. Shunmuga; Singh, S. Christopher Ezhil
ABSTRACT: Biomedical implants are immensely manoeuvered devices that fix various deformities and injuries on medical grounds. With an emergent exploration in this field by researchers, countless combinations of materials have been discovered that perks global mankind. The ultimate goal of this experimentation is to appraise the characteristics of wear and corrosion resistance of Ti–Co–Cr-coated 316L grade austenitic stainless steel (SS) in contrast with TiN-coated and uncoated 316L SS. A micro-abrasion test was conducted on every single sample at 3N, 5N and 7N loads and were characterized in accordance with weight loss, coefficient of friction, surface roughness, Scanning Electron Microscope (SEM) analysis, X-ray Diffraction pattern (XRD), Energy Dispersive X-Ray Analysis (EDAX), Fourier-transform infrared spectroscopy (FTIR) and corrosion resistance. The findings showed that Ti–Co–Cr-coated substrate at 3N load have good mechanical tolerance and offers admirable performance. The corrosion resistance of the specimens divulges the biocompatibility of Ti–Co–Cr as being more distinct because of the existence of titanium metal.